Open innovation in the development of fact-checking agencies during the pandemic (Comunicação & Inovação, 2021)
This research seeks to understand innovative processes in journalism in light of the concept of open innovation and journalistic ecosystem. For this purpose, it systematizes the literature and performs empirical research based on multiple case studies of three fact-checking agencies, Lupa and Aos Fatos (in Brazil) and Chequeado (Argentina), as innovative journalistic actors. The study included the development of products and processes in open innovation as a response to the urgent demand for information and verification of false content in the coronavirus pandemic in 2020.
Keywords: open innovation; journalistic ecosystem; fact-checking